PENERAPAN MODEL PEMBELAJARAN BRAIN BASED LEARNING - Solihat, Amalia; Panjaitan, Regina Lichteria; Djuanda, Dadan (Jurnal Pena Ilmiah, 2017)
This research has background that the lack of student learning result in thermal material, it is caused by the learning process that does not maximalize student brain skill and still relies on the teacher. The efforts used to overcome the problem is Brain Based Learning model. This research aims for performing student learning result. The reaserch object consists of 32 students in Grade IV SDN Bojong Salam II with the first data is only 6,30% that fulfills criteria of KKM. The used research method is Class Measure Research (Classroom Action Research or PTK) with research design of Spiral Kemmis and MC.Target model. The design consists of planning, measuring, obeserving, and reflexing. Based on the research that has been performed, student learning result in 3 cycle has increased becoming 90,36%. The capacity of teacher achieves the goal, i.e 90% and student activity achieves 80% from the goal. It can be concluded that implementation Brain Based Learning model can perform student learning result in thermal material in Grade IV SDN Bojong Salam II.